Analysis of the Feasibility of Education Administration in Elementary Schools - Rosani Djabir; Marwah Marwah; Jamil Jamil (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
Educational administration is the backbone of effective school management. In Pangkajene and Kepulauan (Pangkep) Regency, geographical challenges and the availability of human resources often pose obstacles to meeting administrative standards at the elementary school (SD) level. This study aims to analyze the feasibility of educational administration in elementary schools in Pangkep Regency, covering curriculum administration, student affairs, personnel, facilities and infrastructure, and public relations. This study uses a qualitative descriptive approach with survey techniques. The research subjects included school principals, school administrators, and teachers at 10 sample elementary schools representing mainland and island areas in Pangkep. Data collection was conducted through observation, in-depth interviews, and documentation studies using standard school accreditation instruments. The results of the study show that, in general, the administrative feasibility of education in Pangkep District elementary schools is in the "Sufficiently Feasible" category, with an average achievement rate of 65%. There is a significant disparity between schools in the city center and those in the islands/coastal areas. Specific findings show that: (1) Student affairs and curriculum administration are relatively good; (2) Infrastructure and personnel administration are still weak, especially in relation to data digitization; and (3) The lack of competent administrative staff often results in administrative burdens being shifted to teachers. It can be concluded that administrative management in Pangkep Regency elementary schools still requires systematic improvement, particularly in terms of equal distribution of digital administrative support infrastructure and competency training for school operators.